The effect of visual cues on performance in the ultimatum game in individuals with autism spectrum disorder. (January 2018) - Ikuse, Daisuke; Tani, Masayuki; Itahashi, Takashi; Yamada, Hiroki; Ohta, Haruhisa; Morita, Teppei; Arai, Gousuke; Saga, Nobuyuki; Tokumasu, Takahiro; Ohta, Marie; Sato, Ayaka; Iwanami, Akira
Abstract: The Ultimatum Game (UG) allows for the assessment of altruistic behavior as well as the perception of fairness. We examined the effects of visual social cues (gaze of others), factors associated with autism, and trust on UG performance in typical adults (TAs) and individuals with autism spectrum disorder (ASD). We hypothesized that individuals with ASD would be less affected by visual social cues than TAs. We recruited 30 TAs and 30 individuals with ASD. Participants completed 30 trials of the UG, during which the visual background was altered to include either stylized eyespots, flowers, or a neutral background. Reaction times and money distributed in each condition were recorded. Reaction times did not vary among background conditions in either group, although individuals with ASD responded more slowly overall. TAs distributed less money in the neutral background and flowers conditions than in the eyespots condition, while no significant differences in the amount of money distributed were observed among background conditions for individuals with ASD, who also distributed more money overall than TAs. Such findings may be due to decreased susceptibility to social cues among individuals with ASD. Highlights: We investigated the effects of visual cues in the Ultimatum Game in autism spectrum disorder (ASD). Typical adults (TAs) were altruistic in the game when viewing schematic eyes. Game play of individuals with ASD was not influenced by viewing schematic eyes. Individuals with ASD responded more slowly than TAs. Individuals with ASD distributed more money than TAs.